Brecht in practice theatre, theory and performance - Barnett, David 1968- (London Bloomsbury Methuen Drama, 2015)
"Bertolt Brecht's reputation as a flawed, irrelevant or difficult thinker for the theatre can often go before him to such an extent that we run the risk of forgetting the achievements that made him and his company, the Berliner Ensemble, famous around the world. David Barnett examines both Brecht the theorist and Brecht the practitioner to reveal the complementary relationship between the two.This book aims to sensitize the reader to the approaches Brecht took to the world and the stage with a view to revealing just how carefully he thought about and realized his vision of a politicized, interventionist theatre. What emerges is a nuanced understanding of his concepts, his work with actors and his approaches to directing. The reader is encouraged to engage with Brecht's method that sought to 'make theatre politically' in order to locate the innovations he introduced into his stagecraft. There are many examples given of how Brecht's ideas can be staged, and the final chapter takes two very different plays and asks how a Brechtian approach can enliven and illuminate their production. Ultimately, the book invites readers, students and theatre-makers to discover new ways of apprehending and making use of Brecht"-- Provided by publisher.
"A re-examination of Bertolt Brecht the theatre practitioner in the light of his theoretical writings and his work in the theatre"-- Provided by publisher.
One: Revealing the radical theorist -- Two: The Messingkauf as performative thinking -- Three: Brecht and difference -- Four: Method trumps means -- Five: Brecht and the actor -- Six: Brecht and the director -- Seven: Brecht, documentation and the art of copying -- Eight: Brecht's method in action: The resistible rise of Arturo Ui and closer by Patrick Marber.
Includes bibliographical references and index.
Keywords: Brecht, Bertolt -- 1898-1956 -- Criticism and interpretation